PENYULUHAN TENTANG PENGGUNAAN DAUN AFRIKA (Vernonia amygdalina Del.) SEBAGAI OBAT ASAM LAMBUNG DI PUSKESMAS TALUN KENAS - Wahyudi Wahyudi; Anggun Syafitri; Elysa Elysa (INSTITUT KESEHATAN DELI HUSADA, 2021)
Gastric ulcer is a disease characterized by the presence of ulcers on the gastric mucosal wall which if not treated properly can cause death. African leaves contain tannin compounds that can form a protective layer on ulcers, saponins activate mucous membrane protective factors, and flavonoids that can increase inflammation. prostaglandin production and reduce gastric HCL secretion, all of which play a role in healing gastric ulcers. knowledge about African leaves (varnonia magdolyna del) and the use of plants in the environment around the house that have medicinal properties are also still lacking. The solution offered to overcome this problem is to provide education about African leaf plants (varnonia magdolyna del) and their health benefits in the form of: this activity is carried out by delivering material to the community then a question and answer session is held to ensure that the community understands the material provided. Gastric acid disease is one of the diseases that is often found, weak treatment using synthetic drugs (natural ingredients that are processed in a modern way). Some of them are side effects caused by the high price of synthetic drugs which are not friendly to people with low economy, so knowledge about the use of medicinal plants is very important to have. The results of the counseling in the village of talun kenas are that there are many diseases and are often found in the community, both young and old, one of which is stomach acid. There has been a question and answer session process to ensure understanding of the community about the material presented. The addition of knowledge to the community regarding this extension is seen from the activeness of the community during a discussion session on the type of outreach to the community.